Value chain analysis of onion (Allium cepa) in Miagao, Iloilo. - Clavesillas, Michael Angelo (2016.)
Onions are a major part of Filipino cuisine, and as such have a high level of demand in the Philippine market. To cope with this demand, onions are grown in 22 provinces in the country, notably in Ilocos, Cagayan, and Central Luzon. In Western Visayas, the municipality of Miagao in Iloilo Province is known as the ?Onion Capital of Western Visayas?. This study aims to analyze the value chain of onion produced in Miagao, Iloilo by describing the flow of onions from the farm to the consumers, identifying the various actors involved in the local onion industry and methods practiced during onion marketing, and determining the costs incurred, and the profit margins received along the chain. The data was collected from 107 onion farmers and seven middlemen through guided interviews and focus group discussions. The results showed 3 channels of onion marketing. The farmers were price takers and barely interacted with consumers. Of the 91.71 tons of onions harvested by the farmers in one cropping, 69.31 tons (75.58%) were sold to the market. Farm gate prices of onion during harvest season averaged at P24.249 per kilo, and prices ranged between P11.00 and P45.00 per kilo for good quality onions, while rejected onions (sinisa) fetched priced ranging between P10.00 and P20.00 per kilo. Market prices during this same period averaged at P40.28 per kilo. On average, onion farmers earned a margin of P0.97 per kilo and the middlemen earned a margin of P9.74 per kilo, with assemblers earning P6.31 per kilo, retailers in Miagao earning P9.83 per kilo, wholesaler-retailers in Miagao earning of P8.56 per kilo, and the wholesaler-retailers in Iloilo City earning P13.20 per kilo. Improved irrigation systems can be introduced to increase onion farm yields, and proper storage facilities to increase the storage life of the onions and reduce wastage.
Research Paper (Undergraduate, Bachelor of Science in Economics. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Onions -- Miagao, Iloilo